2023
DOI: 10.1007/s11606-023-08042-5
|View full text |Cite
|
Sign up to set email alerts
|

Facilitators and Barriers Influencing Antipsychotic Medication Prescribing and Deprescribing Practices in Critically Ill Adult Patients: a Qualitative Study

Abstract: Background Antipsychotic medications do not alter the incidence or duration of delirium, but these medications are frequently prescribed and continued at transitions of care in critically ill patients when they may no longer be necessary or appropriate. Objective The purpose of this study was to identify and describe relevant domains and constructs that influence antipsychotic medication prescribing and deprescribing practices among physicians, nurses, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…For instance, delirium during ICU admission is independently associated with a higher mortality risk 1 and may prompt haloperidol treatment. 4 Conversely, sleep disorders are other conditions in which providers may consider to initiate antipsychotics, 4 using sedative anticholinergic agents such as quetiapine. 14 Since our study did not capture these initial triggers for antipsychotic use, residual confounding due to imbalanced baseline prognosis may explain the differences observed between groups for the composite outcome.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…For instance, delirium during ICU admission is independently associated with a higher mortality risk 1 and may prompt haloperidol treatment. 4 Conversely, sleep disorders are other conditions in which providers may consider to initiate antipsychotics, 4 using sedative anticholinergic agents such as quetiapine. 14 Since our study did not capture these initial triggers for antipsychotic use, residual confounding due to imbalanced baseline prognosis may explain the differences observed between groups for the composite outcome.…”
Section: Discussionmentioning
confidence: 99%
“…We used a composite outcome to account for such differential risk; however, the higher risk of the composite outcome may be explained by a true effect of high‐affinity agents or dissimilar indications and underlying prognosis. For instance, delirium during ICU admission is independently associated with a higher mortality risk 1 and may prompt haloperidol treatment 4 . Conversely, sleep disorders are other conditions in which providers may consider to initiate antipsychotics, 4 using sedative anticholinergic agents such as quetiapine 14 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Both doctors and nurses reported they chose to use antipsychotics in anticipation that behavioural symptoms could escalate [ 13 ]. In a similar study, interviews with 21 physicians, nurses and pharmacists in an ICU in Canada also found that reasons given for antipsychotic use were to ensure patient and staff safety, promote sleep and settle patients when staffing was inadequate, and workloads were high [ 14 ]. International guidelines allow for antipsychotic use when safety is a concern and non-pharmacological strategies have not been effective.…”
Section: Introductionmentioning
confidence: 99%